(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
One of the successes of an education is determined by the role of the supporting lecturer of the subject he brings. The supporting lecturer is a bridge and at the same time an agent that allows students to have a dialogue with their world. the role of the supporting lecturer greatly influences the success of students both in terms of academic, non-academic and the spirituality of their religious education. Talking about heavenly things or being said as Spirituality means covering all aspects of life, not only when talking about heavenly things themselves, but also about the profession in the world. The purpose of this study was to demonstrate the effect of hybrid learning-based collaborative learning strategies on the spirituality of Christian Education Faculty of Christian Education Tarutung State Institute for Christian Studies students. This study was designed using the One-Shot Case Study experimental design. The single case study experimental design is an experiment that is used without a comparison and also without a pretest. So based on the results of testing the hypothesis in this study, the regression equation formed is Y = 22.519 + 0.182X. where the tcount (4.918) > ttable (1.9) and the significance number (0.00) <0.05, it can be concluded that H0 is rejected and H1 is accepted, in other words there is an influence of cooperative learning strategies based on hybrid learning on student spirituality.